Inheritance System Mayorat on the Komering Tribe in Urf Perspective - Muhamad Imam Muddin (Nusantara: Journal of Law Studies, 2022)
Purpose in study this there are 2 ( two ) , viz for knowing how system distribution inheritance according to the customs of the Komeringdi tribe Buay Pemuka District Peliung East Oku Regency , South Sumatra Province and for knowing how review Urf about inheritance the customs of the Komeringdi tribe Buay Pemuka District Peliung East Oku Regency , South Sumatra Province . The research method used is normative sociology . Research type this is Field research ( research field ). Informant in study this is the party concerned , chief custom and society local . Based on results study could concluded namely : 1) Implementation inheritance Majority ethnic group Komering in Buay Pemuka District Peliung conducted when heir already died , that is inheritance fall down to child man oldest as expert responsible heir _ answer to his younger siblings as well as family replace role heir (father) as head family . If in a family the no have child man so son-in-law considered man _ or made successor name family the . 2) Review of Islamic Law against implementation system distribution heritage of the Komering Tribe in Buay Pemuka District Peliung East Oku Regency , South Sumatra Province, When reviewed from law inheritance system distribution treasure inheritance mayor ethnic group Komering no can enforced draft inheritance because many difference Among inheritance Islamic law with inheritance ethnic group Komering . In system his inheritance treasure inheritance more dominant inherited to child man whereas child woman get a third just